1986
DOI: 10.1044/jshd.5101.33
|View full text |Cite
|
Sign up to set email alerts
|

Babbling Development of Hearing-Impaired and Normally Hearing Subjects

Abstract: Phonetic transcriptions of babbling samples from 11 normally hearing subjects, age 4-18 months, were compared with samples from 11 hearing-impaired subjects, age 4-28 months. Longitudinal data were available for all hearing babies and for 8 of the 11 hearing-impaired subjects. The analysis focused on two measures: (a) size of consonantal repertoire over time and (b) proportional occurrence of multisyllabic consonant-vowel utterances. On average, the normally hearing subjects evidenced an increase in size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(107 citation statements)
references
References 0 publications
3
103
1
Order By: Relevance
“…Results showed that infants with severe-to-profound hearing loss appear to have explored different types of vocalizations, mainly singletons (consonant-and vowel-like sounds) and GSs in contrast to canonical syllables. These results are consistent with previously reported results on infants with this level of impairment, showing a propensity for singleton consonants, vowels, and GSs and use of few canonical syllables (McCaffrey et al, 2000;Oller, 1986;Stoel-Gammon & Otomo, 1986). Variability in vocalization types across infants increased with increasing hearing loss.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Results showed that infants with severe-to-profound hearing loss appear to have explored different types of vocalizations, mainly singletons (consonant-and vowel-like sounds) and GSs in contrast to canonical syllables. These results are consistent with previously reported results on infants with this level of impairment, showing a propensity for singleton consonants, vowels, and GSs and use of few canonical syllables (McCaffrey et al, 2000;Oller, 1986;Stoel-Gammon & Otomo, 1986). Variability in vocalization types across infants increased with increasing hearing loss.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, landmark infant vocalization studies of the 1980s and early 1990s unequivocally demonstrated that early-vocalization emergence is subject to the influence of hearing sensitivity (Eilers & Oller, 1994;Oller & Eilers, 1988;Stoel-Gammon, 1988;Stoel-Gammon & Otomo, 1986). Canonical babbling is often delayed in infants with hearing loss compared with hearing infants (Eilers & Oller, 1994;Oller & Eilers, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of canonical babbling is delayed in deaf infants, and when it occurs, the babbled utterances differ in duration and timing (Kent et al, 1987;Oller and Eilers, 1988;Oller et al, 1985)" Moreover, the phonetic inventories of deaf infants differ from those of normal infants. Deaf infants rely on sounds that are visually prominent, such as /ba/ and /ma/, to a greater extent than normal infants (Stark, 1983;Stoel-Gammon, 1988;Stoel-Gammon and Otomo, 1986). The role of audition in the learning of vocalization is also suggested by the fact that adult speakers of the language speak the dialect produced locally.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been clarified that the auditory experience plays an important role in the development of mature syllables [Clement and Koopmans-van Beinum, 1995;Eilers and Oller, 1994;Oller et al, 1985;Oller and Eilers, 1988;Stoel-Gammon and Otomo, 1986]. Oller and Eilers [1988] compared the phonological characteristics of the vocal behavior of 9 deaf infants with that of 21 hearing infants.…”
Section: Introductionmentioning
confidence: 99%